INFLUENCE OF PRODUCT INNOVATION AND SERVICE QUALITY ON PURCHASE DECISION IN JAMBI ARINY BATIK IN KELURAHAN PASIR PANJANG JAMBI KOTA SEBERANG - Agesha Marsyaf (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
Batik is a national cultural asset that has been inherited from generation to generation to every generation until now. Batik represents one of the creative handicraft industries in Indonesia which is rooted in culture and is able to provide employment and entrepreneurship in Indonesia, one of which is the Jambi area. Like other products, in order to be able to compete in the Jambi batik product market, it is necessary to understand the market's needs. Therefore, the authors took the title